Pelaksanaan Fungsi Perbankan Dalam Penyaluran Kredit di Sektor Kemaritiman - Marnia Rani (Jurnal Selat, 2015)
Indonesia is a maritime country with an area of ocean roughly two-thirds of the total area of the archipelago. Likewise, with the Riau Islands Province whose territory is surrounded by oceans. With the demographic conditions, the population in the Province of Riau Islands, especially Tanjungpinang, mostly working as a fisherman. To support the living standards of fishermen are still far from prosperous, the necessary funding from various parties, especially banks that have the function of lending or financing based on Islamic principles. Expected by the function, the bank can provide the widest access for fishermen to the maritime economic development centered on the fishermen can be realized. This study classified normative legal research with descriptive type of explanatory and analytical approach to normative legal substance (approach of legal content analisys). Necessary data is secondary data consists of primary legal materials, secondary law and tertiary legal materials collected from the literature. The data is processed by editing, coding, and systematization of data, then analyzed using qualitative methods. Based on the results of research and discussion, that the regulation of banking activities in fund lending to the public regulated in Law No. 7 of 1992 on Banking as amended by Act No. 10 of 1998. Conventionally, banks can conduct business loans to community in the form of credit. Likewise, based on Sharia Principles, commercial anks and rural banks can provide financing and fund placement based on Sharia Principles, in accordance with the provisions stipulated by Bank Indonesia. Fund Lending in the maritime sector, especially for fishermen implemented through credit programs Food Security and Energy and the People’s Business Credit which is the implementation of government programs through the bank’s status as a state-owned enterprise. In terms of the distribution of funding with Islamic principles, There are private banks in Tanjungpinang which has given the finance portfolio to some fishermen in Tanjungpinang. Keywords: Banking, Credit, Maritime